Relationship Between Oil Price, Exchange Rate, And Stock Market - Kehkashan Nizam (International Journal Of Economics Social And Technology, 2022)
The purpose of this study is to investigate the impact of oil prices and their fluctuation on the exchange rate and stock prices in Pakistan. The time-series data were collected from 1995 to 2018. The data will collect from World Bank and the Pakistan stock exchange (PSX). Oil price and oil price volatility are independent variables and dependent variables are the exchange rate and stock price. Descriptive statistics, unit root test, and ordinary least square OLS regression has applied for this research. The results from Model 1 show that there is a negative impact of oil price volatility OPV on stock price SP in Pakistan. The oil price has a positive impact on SP in Pakistan. The results suggest that increases in the OP lead to increases in the SP. in contrast increases the volatility in OP reduces the SP. Moreover, Model 2 results represent, as the impact of oil price volatility OPV is negative on exchange rate ER in Pakistan, while the oil price has a positive impact on exchange rate ER in Pakistan. The results suggest that increases in the OP lead to increases in the ER. In contrast, increasing or decreasing the volatility in OP reduces or increases the ER.  This research will be very helpful for company owners, businesspeople, managers, policymakers, academic and industry researchers, and individual investors to reduce uncertainty and volatility in the financial market. The finding suggested that the study would help in managing and measuring divestment risk present in the market, selecting stock or portfolio, and financial derivatives pricing